Analysis Of Explosion Severity Of Tea Powder At Different Particle Size And Concentration In A Confined Space - Nur Hikmah, Semawia; Siti Zubaidah, Sulaiman; Siti Kholijah, Abdul Mudalip; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad (UTM Press, 2022)
Tea contains compounds rich in carbon-hydrogen bonds. When tea dust is suspended in air, across a variety of particle sizes and concentrations, in the presence of spark, it can combust, therefore presenting an explosion hazard. The explosion pressure properties of tea dust of four different dust concentrations (1000 g/m³, 1500 g/m³, 2000 g/m³ and 2500 g/m³) were conducted in a 20-L spherical explosion test vessel under five distinct particle sizes (71 µm, 125 µm, 160 µm, 180 µm and 250 µm). According to the findings, the explosion pressure characteristic is strongly related to dust concentration and particle size. Moisture content also has an effect on explosion propagation. The dried tea dust reached the maximum explosion pressure faster than undried tea dust. Among of the concentration and particle size range tested, the highest explosion pressure, 14.6 bar, was recorded at 2000 g/m³ with particle size 125 μm. The explosion index was 222 bar/s. It was shown that at higher dust concentration (≥2000 g/m3) and smaller particle sizes (≤125 μm) the explosion became more severe, whereby the flame accelerated at a higher rate and raised the explosion pressure drastically. The pressure characteristic changed as the conditions in which they occurred changed. These analyses and predictions are essential for achieving safe and optimal performance of tea manufacturing technology as well as the development of new applications.